Anion exchange strategy to improve electrocatalytic hydrogen evolution performances in cationic metal–organic frameworks. Issue 47 (24th November 2021) - Li, Bei; Lei, Qingjuan; Qin, Tong; Zhang, Xiaoxian; Zhao, Dongsheng; Wang, Feng; Li, Wenqian; Zhang, Zhengguo; Fan, Liming
Abstract : Through an anion exchange strategy, the post-synthetic cationic metal–organic frameworks present better electrocatalytic performances during the hydrogen evolution reaction process than the pristine one. Abstract : A stable cationic metal–organic framework (MOF) based on a neutral multidentate N-ligand and Ni(ii ) metal center has been successfully synthesized. The cationic MOF can effectively capture anions (MnO4 − and CrO4 2− ) from water through an anion exchange strategy. It is noteworthy that the post-synthesized cationic MOFs present better electrocatalytic performances for the hydrogen evolution reaction (HER) compared with the pristine MOF.